(untitled) (Global Journal of Human-Social Science, 2020)
The main thrust of this study was to examine activities of Sea Robbers and its implication on water transportation in Niger Delta Region of Nigeria. A multi-stage sampling technique was employed to select respondents from three littoral states in the region. The population of the study comprised maritime business operators, and a sample size of 400 was derived using the Taro Yamane sample size determination technique. Questionnaires and oral interviews were the instruments used for data collection. The hypothesis formulated for the study was tested using Pearson Product Moment Correlation Coefficient (PPMC). Findings from the study revealed that there is a significant relationship between Sea Robbers and water transportation. This implies that the activities of sea robbers in the region are alarming. If left unrestrained, will frighten seafarers/ tourists from travelling by water as well as hinder commercial and socio-cultural activities. Consequently, problem oriented policing at hotspots along creeks and waterways in the region is recommended.